Pubic Arch Angle Measurement by Transperineal Ultrasonography: A Prospective Cross-Sectional Study - Raimundo Homero Carvalho Neto; Antonio Brazil Viana Junior; Antonio Fernandes Moron; Edward Araujo Júnior; Francisco Herlânio Costa Carvalho; Helvécio Neves Feitosa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective To evaluate the ability of the pubic arch angle (PAA) as measured by transperineal ultrasonography during labor to predict the delivery type and cephalic pole disengagement mode. Methods The present prospective cross-sectional study included 221 women in singleton-gestational labor ≥ 37 weeks with cephalic fetuses who underwent PAA measurement using transperineal ultrasonography. These measurements were correlated with the delivery type, cephalic pole disengagement mode, and fetal and maternal characteristics. Results Out of the subjects, 153 (69.2%) had spontaneous vaginal delivery, 7 (3.2%) gave birth by forceps, and 61 (27.6%) delivered by cesarean section. For the analysis, deliveries were divided into two groups: vaginal and surgical (forceps and cesarean). The mean PAA was 102 ± 7.5º (range, 79.3-117.7º). No statistically significant difference was observed in delivery type (102.6 ± 7.2º versus 100.8 ± 7.9º, p = 0.105). The occipitoanterior position was seen in 94.1% of the fetuses and the occipitoposterior position in 5.8%. A narrower PAA was found in the group of surgical deliveries (97.9 ± 9.6º versus 102.6 ± 7.3º, p = 0.049). Multivariate regression analysis showed that PAA was a predictive variable for the occurrence of head disengagement in occipital varieties after birth (odds ratio, 0.9; 95% confidence interval, 0.82-0.99; p = 0.026). Conclusion Ultrasonographic measurement of the PAA was not a predictor of delivery type, but was associated with the persistence of occipital varieties after birth.